2000
DOI: 10.1111/j.1365-2125.2000.00179.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic‐pharmacodynamic evaluation of ceftazidime continuous infusion vs intermittent bolus injection in septicaemic melioidosis

Abstract: Aims  Experimental studies have suggested that constant intravenous infusion would be preferable to conventional intermittent bolus administration of beta‐lactam antibiotics for serious Gram‐negative infections. Severe melioidosis (Burkholderia pseudomallei infection) carries a mortality over 40% despite treatment with high dose ceftazidime. The aim of this study was to measure the pharmacokinetic and pharmacodynamic effects of continuous infusion of ceftazidime vs intermittent bolus dosing in septicaemic meli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…[6] In addition, several studies have evaluated clinical outcomes including severity of illness, duration of mechanical ventilation, mortality, clinical cure from actual infection, time to normalization of leukocytosis or pyrexia and lengths of ICU stay. [822] Similar to other studies,[11202327] no significant differences were found between the CI ( n = 31) and the II ( n = 30) groups in terms of sex, age, APACHE II score at ICU admission, diagnosis and microorganism responsible for VAP in this study. Consequently, mortality is not mainly dissimilar in the continuous and intermittent dosed groups.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[6] In addition, several studies have evaluated clinical outcomes including severity of illness, duration of mechanical ventilation, mortality, clinical cure from actual infection, time to normalization of leukocytosis or pyrexia and lengths of ICU stay. [822] Similar to other studies,[11202327] no significant differences were found between the CI ( n = 31) and the II ( n = 30) groups in terms of sex, age, APACHE II score at ICU admission, diagnosis and microorganism responsible for VAP in this study. Consequently, mortality is not mainly dissimilar in the continuous and intermittent dosed groups.…”
Section: Discussionsupporting
confidence: 89%
“…Consequently, mortality is not mainly dissimilar in the continuous and intermittent dosed groups. [81113142027] Rapid improvement in PaO 2 /FiO 2 has been granted as the most precise marker for adequate treatment. Duration of treatment was directly associated with the CPIS score at the time of pulmonary infection diagnosis in the Micek et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining studies included patients receiving continuous infusion β-lactams [3,4,9,11,15-17,19,20,22,23]. Six studies used the same total daily dose of β-lactams in both study arms [9,15,17-20].…”
Section: Resultsmentioning
confidence: 99%
“…Even when using CI, the combination of pathogens with MICs close to the susceptibility breakpoint and critically ill patients with lower than expected Css (because of increased Vd and increased drug clearance) can lead to critically low Css/MIC ratios below the advised ratio of 2.5 to 4. An overview of studies [11,15,25-33] investigating PK-parameters of continuous infusion of different antimicrobials in critically ill patients is shown in Table 1. In most of these studies, the Css/MIC ratio is well above 2.5.…”
Section: Reviewmentioning
confidence: 99%